Applications and usability of interactive TV : 8th Iberoamerican Conference, jAUTI 2019, Rio de Janeiro, Brazil, October 29-November 1, 2019, Revised Selected Papers /: 8th Iberoamerican Conference, jAUTI 2019, Rio de Janeiro, Brazil, October 29-November 1, 2019, Revised Selected Papers. ([2020]) - Unknown
No abstract available